Ultrasonography guided puncture and dilatation in membranous rectal atresia - Cunera M.C. de Beaufort; Joep P.M. Derikx; Simon G.F. Robben; Rick R. van Rijn; Ramon R. Gorter; L.W. Ernest van Heurn (Elsevier, 2023)
Purpose: Rectal atresia (RA) is a rare type of anorectal malformation (ARM), occurring in 1-2% of ARM. Discussion remains on optimal treatment strategy for RA. The aim of this study was to present a minimally invasive method to treat patients with membranous RA: ultrasonography guided puncture and dilatation. Cases: Three children are described (1 female, and 2 male). All patients were diagnosed with membranous RA, and treated with ultrasonography guided puncture and dilatation within 48 hours after birth. The procedure was performed under sedation and was uncomplicated in all patients. Follow-up showed good bowel function in 2 of 3 patients. One patient had persistent constipation needing laxative treatment up to the age of 6 years. Conclusions: Rectal atresia is extremely rare, and little is known on optimal treatment methods. Ultrasonography guided puncture and dilatation is a minimally invasive technique to potentially adequately treat patients with membranous RA. In our patients, this treatment strategy has shown to be effective with good long-term outcomes regarding bowel function. Further research should be performed to further investigate optimal treatment for the different types of RA. Level of Evidence: V